Kort til Balduin MÃ¶llhausen's Rejse fra Mississippi til Sydhavets Kyster i Aarene 1853 1854. - Th. Berg's lith. Inst. (Th. Berg's lith. Inst., 1858)
Map shows eastern route of Heinrich Balduin Mollhausen across the southwestern United States from the Mississippi River to the Pacific Coast during 1853 and 1854. Areas of Native American habitation, military posts, and settlements are noted. Insets: [Map of the mid-western states] and "Profil fra Ft. Smith til Sydhavet" [More of Ft. Smith to the Southern Ocean]. Scale [1:6,015,000].